Tinjauan Yuridis Tindak Pidana Cybercrime Berdasarkan Hukum Pidana - Akem Doristu Engla; Lardson Dean; Nanda Rizky Rilandi; Raihana Raihana (International Forum of Researchers and Lecturers, 2023)
The rapid development of information and communication technology produces a multifunctional internet. This development brings us to the threshold of the fourth revolution in the history of human thought, when viewed from the construction of human knowledge which is characterized by a borderless way of thinking. The acceleration of technology is increasingly increasing which is the material cause of continuous change in all interactions and activities of the information society.